Changes in lifestyle among prostate cancer survivors: A nationwide population‐based study. Issue 10 (1st September 2020) - Bergengren, Oskar; Enblad, Anna Pia; Garmo, Hans; Bratt, Ola; Holmberg, Lars; Johansson, Eva; Bill‐Axelson, Anna
Abstract: Objective: Long‐term information on lifestyle changes among prostate survivors is lacking. In this nationwide, population‐based study we investigated the prevalence of lifestyle changes, factors associated with lifestyle changes and associations between lifestyle changes and general quality of life. Methods: All men registered in the National Prostate Cancer Register of Sweden diagnosed in 2008 with low‐risk prostate cancer at age 70 years or younger were sent a questionnaire. Logistic regression was used to calculate odds ratios (ORs) with 95% confidence intervals for factors potentially associated with lifestyle change. Results: Out of 1288, 1720 men (75%) were responded. A total of 279 (22%) reported a positive lifestyle change regarding diet or exercise. Poor functional outcomes after treatment was associated with exercising less (OR 1.6, 95% CI 1.2‐2.1) and less interest in social activities and relationships (OR 1.8, 95% CI 1.5‐2.1). Men who exercised more (OR 7.9, 95% CI 4.4‐14) and men who had an increased interest in relationships and social activities (OR 5.2, 95% CI 2.1‐13) reported higher general quality of life. Conclusions: A considerable proportion of men reported making positive lifestyle changes after the prostate cancer diagnosis. The time after diagnosis may be a teachable moment that facilitates lifestyle interventions. Poor functional outcomes after treatment may reduce the willingness to engage in positive lifestyle change, which need be considered when supporting men after treatment. Men who made a positive lifestyle change, regardless of whether it was exercise or regarding relationships and social activities more often reported a high level of general quality of life.